2009
DOI: 10.1088/0031-9155/54/7/007
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of respiratory tidal volume based on the external torso volume change: a potential volumetric surrogate

Abstract: An external respiratory surrogate that not only highly correlates with but also quantitatively predicts internal tidal volume should be useful in guiding four-dimensional computed tomography (4DCT), as well as 4D radiation therapy (4DRT). A volumetric surrogate should have advantages over external fiducial point(s) for monitoring respiration-induced motion of the torso, which deforms in synchronization with a patient-specific breathing pattern. This study establishes a linear relationship between the external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…Simple scalar surrogate signals have been derived from skin surface data by tracking a single point on the skin surface (Hughes et al, 2009), or by calculating the volumes under the skin surface (Hughes et al, 2009;Li et al, 2009;McClelland et al, 2011). It has been shown that calculating the volume under the skin surface produces a signal similar to that obtained via spirometry, but without the drift often seen in spriometry signals Hughes et al, 2009).…”
Section: Deriving Simpler Surrogate Data From High Dimensional Datamentioning
confidence: 99%
“…Simple scalar surrogate signals have been derived from skin surface data by tracking a single point on the skin surface (Hughes et al, 2009), or by calculating the volumes under the skin surface (Hughes et al, 2009;Li et al, 2009;McClelland et al, 2011). It has been shown that calculating the volume under the skin surface produces a signal similar to that obtained via spirometry, but without the drift often seen in spriometry signals Hughes et al, 2009).…”
Section: Deriving Simpler Surrogate Data From High Dimensional Datamentioning
confidence: 99%
“…The volume‐conserving organs, such as the heart, liver, and stomach, do not change their volume with the respiratory motion, although they may deform, because non‐lung tissues are not compressible under respiratory pressure difference (3–6 mmHg) 48. Therefore, the delineated OAR volumes are expected to be constant.…”
Section: Methodsmentioning
confidence: 99%
“…The BP ( BP = ΔV thx /TV ), defined as the lung volume expansion change (AP) divided by the TV change, was used to quantify the involvement of the thorax (36, 37) and abdomen (1 – BP) in respiration. Therefore, the BP is a critical parameter that introduces directional information into the scalar spirometric TV data.…”
Section: Methodsmentioning
confidence: 99%
“…Because only motion variation caused by irregularity was calculated, the computation workload was significantly reduced (34, 35). Additionally, separating the superoinferior (SI) from anteroposterior (AP) motions using breathing patterns (36, 37) simplified RMP modeling computation. The baseline tumor motion can be obtained from 4-dimensional computed tomography (4DCT) at simulation, and the motion perturbation can be calculated using the respiratory changes in TV and BP fed by the OSI-based technique (20, 21) during treatment.…”
Section: Introductionmentioning
confidence: 99%